Electromyographic intra individual variability in front crawl swimming - Martens, J.; Daly, D.; Fernandes, R. J.; Deschamps, K.; Staes, F. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to assess the intra-individual variability of two bilaterally measured EMG signals (deltoideus medialis and rectus abdominis) in front crawl swimming and compare the influence of the normalization technique on several variability measures. Fifteen well-trained adult male competitive swimmers were tested and four additional measures of variability besides mean and standard deviation were calculated. The repeatability of swimming movements was high for both tested muscles and one stroke cycle might be sufficient to determine a swimmers movement pattern. Variance ratio was suggested as a preferred additional measure of variability as it was least susceptible to differences in normalization method.